(untitled) (Studia Prawnicze / The Legal Studies, 2001)
Skala i liczba masowych naruszeń praw człowieka na świecie bynajmniej nie maleje. Czy oznacza to, że ewolucja systemu ONZ mającego na celu zapobieganie temu zjawisku nie przynosi pożądanych rezultatów? Wydawałoby się, że jest to oczywista konkluzja. Oceniając te zmiany, trzeba jednak pamiętać, że większość wprowadzono bardzo niedawno. Na ich efekty trzeba będzie jeszcze poczekać. Warto również mieć świadomość, że skuteczność tych środków zależy w decydującej mierze od współpracy rządów i od ich woli politycznej. Dopóki rządy wielu państw będą skłonne raczej poszukiwać spokojnego (relatywnie ostatnio) portu suwerenności narodowej aniżeli współpracy ze wspólnotą międzynarodową w poszukiwaniu rozwiązania ich problemów, dopóty kryzysy dotyczące ich społeczeństw będą się, niestety, powtarzać. The scale and number of massive human rights violations around the world is by no means decreasing. Does this mean that the evolution of the UN system to prevent it does not have the desired effect? This would seem the obvious conclusion. In assessing these changes, however, it is important to bear in mind that most were introduced very recently. Their effects will still have to be seen. It is also worth noting that the effectiveness of such measures depends critically on the cooperation of governments and their political will. As long as the governments of many countries are inclined to seek a quiet (relatively recently) harbour of national sovereignty rather than cooperation with the international community in the search for a solution to their problems, the crises affecting their societies will, unfortunately, continue.